The supramolecular chemistry of handcuff rotaxanes and deteriorating leather - Tarnowska, Marysia (2023)
Supramolecular chemistry deals with systems made of distinct chemical species which, when put together, have different properties than each individual component. These species are often not bonded in a covalent or ionic sense, but are based on host-guest chemistry. Mechanically interlocked molecules (MIMs) and handcuff rotaxanes in particular, which are systems containing multiple covalently bonded macrocycles, through which a rod is threaded then stoppered, are an example of such species. MIMs have wide ranging applications in nanoscale electronics, systems which mimic biology, and many others. Since its recent discovery, pillar[5]arene has been used extensively in MIMs due to its interesting host guest properties, and this work deals with handcuff rotaxanes containing it, as well as perylene diimide (PDI), tetrazine, and imidazole groups.